Assessing and Extending Colorblind Racism Theory Using National Survey Data. Issue 2 (April 2022) - Hamilton, Amber M.; Hartmann, Douglas; Larson, Ryan
Eduardo Bonilla-Silva's work on colorblind racism has become a prominent theoretical framework for analyzing racial attitudes, ideologies, and discourses in the contemporary United States. However, the scholarship has yet to produce an empirically rigorous, quantitative assessment of colorblind racism to document the theory's generalizability and assess it as a theory of racial attitudes. In this article, we build upon the rich body of qualitative research to develop a novel measurement model of colorblind racism using nationally representative survey data. We then use the model to estimate the impact of adherence to colorblind beliefs on support for affirmative action policies and awareness of structural disadvantage. Our findings indicate a good model fit, and that awareness of structural disadvantages acts as a mediator between colorblind racism and affirmative action support. We use our findings to develop colorblind racism theory, especially regarding structural disadvantage, both empirically and theoretically; we also consider the implications of these findings and colorblind theory more generally for the study of racial attitudes in the post-Trump era.